Computational modeling of objects presented in images : fundamentals, methods, and applications : 6th International Conference, CompIMAGE 2018, Cracow, Poland, July 2-5, 2018, Revised selected papers /: fundamentals, methods, and applications : 6th International Conference, CompIMAGE 2018, Cracow, Poland, July 2-5, 2018, Revised selected papers. ([2019]) - Unknown
No abstract available